Pengaruh WorkFamily Conflict terhadap Job Performance dengan Employee Satisfaction sebagai Variabel Intervening - Cintya Mega Sulistyowati; Hafid Kholidi Hadi (Jurnal Ilmu Manajemen, 2021)
The study aims to test and explain the impact of work-family conflict on job performance through employee satisfaction as an intervening variable of a female nurse who works in a hospital in Surabaya. This type of research is a causal analysis using a quantitative approach. Questionnaires were distributed to 32 employees using simple random sampling techniques”data collected by a questionnaire using a Likert scale. Questionnaires were distributed via electronics to the respondents. The analytical method used in this study is partial least square (PLS) with SmartPLS 3.3.2 software. The results showed that work-family conflict had a significant effect on employee satisfaction. The work-family conflict had a negative effect on job performance. Employee satisfaction had a significant positive effect on job performance. Employee satisfaction as an intervening variable affects the relationship between work-family conflict and job performance. Hospitals should improve their HR management system by adding counselling methods that positively impact nurse work-family conflict management and maintain nurse satisfaction and performance.